Labor Relations Boards and the Courts - Weatherhill, J. (Relations industrielles / Industrial Relations, 1966)
The Canada Labour Relations Board and most of our provincial Boards are protected in the determination of the matters coming before them by « privative clauses ». The author questions the effect of such clauses on the endeavours of the Boards and more directly on their real jurisdiction.